Financial Management Training Well And Meticulously In Pengalangan Village To Improve Family Finances - ambarwati, nadya; Rahayu, Asti; Kamilia, Abidatul (JURNAL PENGABDIAN TEKNOLOGI TEPAT GUNA, 2023)
The implementation of this PKM (Community Service) activity is about how to manage finances well and carefully in the family, which was implemented in September 2023 targeting residents of Pengalangan Gresik village, East Java. Financial management in the household is an absolute thing that must be implemented and carried out, to avoid financial management mistakes in the family such as wasting money in buying things that are not necessary. The management not only from the permanent sources of funds but also the non-fixed sources of funds, as well as how to manage their expenditure. The aim of this community service activity is sharing and providing knowledge regarding money management in the family, especially for Pengalangan village residents. Gresik, East Java.